2016
DOI: 10.2224/sbp.2016.44.5.827
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Coping, and Mental Health: a Bayesian Network Model Analysis

Abstract: We examined the relationships among gender, coping, and mental health in terms of probabilities. We selected a sample of university students (N = 131) aged between 18 and 32 years, and used the GHQ-28 and COPE instruments for analysis. The Bayesian network model that we constructed showed higher probabilities of symptoms of mental health problems for emotion-focused coping than for problem-focused coping. No differences were found regarding gender. This suggests that the use of problem-focused coping is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…In the literature, studies investigating mental disorders and coping skills had different results. While some studies found that individuals with mental disorders use effective coping skills (Cohen, Hassamal, & Begum, ; Gloria & Steinhardt, ), the others found the use of ineffective coping skills (Adan, Antúnez, & Navarro, ; Aksoy & Kelleci, ; Mingrone et al., ; Moret‐Tatay, Beneyto‐Arrojo, Laborde‐Bois, Martínez‐Rubio, & Senent‐Capuz, ). In another study, it was determined that both methods were used together (Shrestha, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, studies investigating mental disorders and coping skills had different results. While some studies found that individuals with mental disorders use effective coping skills (Cohen, Hassamal, & Begum, ; Gloria & Steinhardt, ), the others found the use of ineffective coping skills (Adan, Antúnez, & Navarro, ; Aksoy & Kelleci, ; Mingrone et al., ; Moret‐Tatay, Beneyto‐Arrojo, Laborde‐Bois, Martínez‐Rubio, & Senent‐Capuz, ). In another study, it was determined that both methods were used together (Shrestha, ).…”
Section: Discussionmentioning
confidence: 99%
“…Coping has been defined by Lazarus and Folkman [29] as the behavioral and cognitive efforts one uses to manage the demands of a stressful encounter. Current theory on coping underlines that coping involves a mixture of conscious cognitive and behavioral strategies of responding to negative events [30,31]. Nevertheless, according to Garnefski et al [32], cognitive appraisal processes might precede the process of taking behavioral actions.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of occupational health and safety, the one that concerns us, there are several examples of the application of Bayesian networks. As examples, Zhou et al [ 52 ] proposed a model to analyze the influence of climate safety factors and personal experience on human behavior; Yang et al [ 53 ] evaluated the relationship between psychological factors and successful smoking cessation; Akhtar and Utne [ 54 ] calculated the risk of human fatigue in maritime accidents; García-Herrero et al [ 55 ] analyzed the influence of working conditions on occupational accidents; Moret-Tatay et al [ 56 ] examined the relationships, in terms of probabilities, between gender, coping, and mental health.…”
Section: Introductionmentioning
confidence: 99%